Adsorption and release of micronutrients by humin extracted from peat samples - Goveia, Danielle [UNESP]; Melo, Camila de A. [UNESP]; De Oliveira, Lilian K. [UNESP]; Fraceto, Leonardo F. [UNESP]; Rocha, Julio Cesar [UNESP]; Filho, Newton Luiz Dias [UNESP]; Rosa, André Henrique [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2013)
The objective of this work was to investigate the adsorption of micronutrients in humin and to verify the ability to release these elements in water. The first step was to determine the adsorption capacity of humin for several essential plant micronutrients and check the kinetic parameters. The order of adsorption was Zn < Ni < Co < Mn < Mo < Cu < Fe, whereas Zn showed maximum values of ca. 2.5 mg g-1 and Fe values of ca. 0.5 mg g-1 for systems containing 1 g of humin. Iron presented higher percentages of release (ca. 100%) and Co the lowest percentages (0.14%). The findings suggested that the use of humin enriched with micronutrients can be a promising alternative for the fertilization of agricultural soils, with the additional benefit of incorporating organic matter present in the form of humic substances into the soil and improving the agricultural productivity. © 2013 Sociedade Brasileira de Química.
Keywords: Adsorption; Desorption; Humin; Micronutrients